The physiological ramifications of chorionic somatomammotropin RNA interference - Tanner, Amelia R., author; Anthony, Russell V., advisor; Rozance, Paul J., advisor; Engle, Terry E., committee member; Thomas, Milton G., committee member; Winger, Quinton A., committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.
Keywords: chorionic somatomammotropin; intrauterine growth restriction; blood flow; placenta; glucose